Elucidating Cathode Degradation Mechanisms in LiNi0.8Mn0.1Co0.1O2 (NMC811)/Graphite Cells Under Fast Charge Rates Using Operando Synchrotron Characterization. Issue 2 (1st February 2022) - Quilty, Calvin D.; West, Patrick J.; Wheeler, Garrett P.; Housel, Lisa M.; Kern, Christopher J.; Tallman, Killian R.; Ma, Lu; Ehrlich, Steven; Jaye, Cherno; Fischer, Daniel A.; Takeuchi, Kenneth J.; Bock, David C.; et al.
Abstract : Li-ion batteries capable of extreme fast charging (XFC) are in demand to facilitate widespread electric vehicle (EV) adoption. While the impact of fast charge on the negative electrode has been studied, degradation of state-of-the-art NMC811 under XFC conditions has not been studied in detail. Herein, cathode degradation is probed in NMC811/graphite batteries by analysis of structural and chemical changes for recovered samples previously cycled under XFC conditions and during typical cycling. NMC surface reconstruction, as determined by soft X-ray absorption, was not detected for recovered electrodes. However, bulk redox activity from X-ray absorption near edge structure measurements showed more change in the oxidation state of Ni and Co under the 1C charge rate compared to the 4C rate consistent with the electrochemistry. Increased unit cell volume contraction under the 1C rate as determined by operando X-ray diffraction suggests that higher charge rates may provide a protective effect on the cathode by reducing structural distortion due to less delithiation.